The trade, development and cooperation agreement between the Republic of South Africa and the European Union : an analysis with special regard to the negotiating process, the contents of the agreement, the applicability of WTO law and the Port and Sherry Agreement - Volz, Eckehard (Stellenbosch : Stellenbosch University, 2012)
Thesis (LLM)--University of Stellenbosch, 1999.